What shapes the mammal species poaching in protected areas: biophysical or anthropogenic factors? A case study in Pendjari Biosphere Reserve - DEGBELO, Galvius Finagnon; DJAGOUN, CHABI A.M.S.; TOYI ALAGBE, S. SCHOLASTIQUE MIREILLE; KOUTON, Meryas Dègbémabou; Padonou, E.A.; SINSIN, Brice (My University, 2022)
Understanding what shapes the mammal species poaching in protected areas is critical to developing targeted management strategies for reducing poaching. We collected the data for poaching incidents on the GPS coordinates from 2011 to 2017 to map poaching incidents in the Pendjari Biosphere Reserve. Poaching incidents were then related to environmental and anthropogenic variables using regression analyses. The study shows that poaching is more concentrated along the main river in the Pendjari National Park. Only nearest distance to the main river significantly predicted the location of high poaching incidents. These results could be used as the starting point by the park managers when planning the anti-poaching activities.
Keywords: Benin; GIS layers; Pendjari Biosphere Reserve; poaching incidents; wildlife